Measuring the 'financing gap' of European corporations. An update - Federico Galizia (European Investment Bank (EIB), 2003)
The 'financing gap' measures the need of external funds for the corporate sector as the difference between gross 'capital formation' and 'savings'. Taking advantage of the recent release of data in the ESA95 standard, this paper assembles a set of stylized facts about the corporate financing gap for the main European economies and for the Euro area as a whole. Notably, quarterly data on bank lending to the Euro corporate sector from the European Central Bank enable analysis of the evolution over the current phase of the business cycle. The results update and are consistent with previous findings from data in the ESA79 standard (which cover the period 1970-97 and are discussed in a companion study entitled 'The Savings Gap of European Corporations. A first look at the available data'). In particular: (i) a large majority of investment remains funded from internal sources and (ii) bank lending is the principal source of external finance. However, the fact that (iii) loans to corporates tend to overshoot the financing gap during an upturn emerges more clearly in the recent cycle than it did in previous ones.
Keywords: 330